IBD-INFO Questionnaire: A Multicenter French Up-to-Date Survey of Patient Knowledge in Inflammatory Bowel Disease. Issue 5 (1st March 2018) - Danion, Pauline; Buisson, Anthony; Roblin, Xavier; Mathieu, Nicolas; Charlois, Anne-Laure; Borgerding, Joshua N; Williet, Nicolas; Del Tedesco, Emilie; Flourié, Bernard; Nancey, Stéphane; Boschetti, Gilles
Abstract: Background: It has been demonstrated in many chronic conditions, including inflammatory bowel disease (IBD), that better patient knowledge about pathology and treatment improves the course and management of disease. The aim of this study was to develop an updated self-questionnaire to assess patients' level of knowledge of IBD. Methods: The IBD-INFO included 3 parts: an original part (Q1) and 2 parts from the translation of the preexisting questionnaires Crohn's and Colitis Knowledge score (CCKNOW) (Q2) and Crohn's and Colitis Pregnancy Knowledge score (CCPKNOW) (Q3). The reliability and discriminatory ability of the questionnaire were validated in 3 groups of non-IBD volunteers with various theoretical knowledge levels. The final questionnaire (64 validated questions) was then tested on 364 in- and out- IBD patients from 4 French university hospitals. The score for each part of the questionnaire was calculated, and factors associated with low scores were identified by univariate and multivariate logistic regression analyses. Results: The scores obtained by the 3 non-IBD volunteer groups differed significantly ( P < 0.0001), and the IBD-INFO questionnaire showed excellent internal reliability and consistency (α = 0.98). The median total score obtained by the IBD patients was 27/64 (range, 0–59), and scores for Q1, Q2, and Q3 were, respectively, 10/23 (range, 0–21), 11/24 (range, 0–23), and 4/17 (range, 0–16). In multivariate analysis, lack of a university degree, not being a member of a patient association, not receiving anti–tumor necrosis factor alpha (anti-TNFα) treatment, duration of IBD ≤3 years, male sex, and age >38 years were independent risk factors of a poor IBD-INFO knowledge score. The areas of knowledge least mastered were vaccination, IBD-related cancers, treatments, and pregnancy. Conclusions: Using the IBD-INFO, an updated self-administered questionnaire built to assess IBD patients' knowledge, several risk factors have been highlighted that allow better targeting of patients and areas requiring an improvement in the level of information.